Personal Branding: Interdisciplinary Systematic Review and Research Agenda - Gorbatov, Sergey; Khapova, Svetlana N.; Lysova, Evgenia I. (Frontiers in Psychology, 2018)
Personal branding has become an important concept in management literature in recent years. Yet, with more than 100 scholarly papers published on the concept to date, it has developed into a fragmented area of research with a diversity of definitions and conceptual boundaries. This paper posits that this heterogeneity of extant research impedes theoretical and empirical advancement. To strengthen the foundation for future work, we review the extant literature and offer an integrative model of personal branding. Through our systematic literature review we identify the key attributes of the construct, establish its clarity by comparing it with similar concepts in its nomological network, and suggest the definitions of personal branding and personal brand based on the reviewed literature. Further, we propose a theoretical model of personal branding summarizing the findings from the reviewed papers. The proposed model outlines the trends conducive to personal branding, as well as its drivers, processes, and outcomes. Finally, we discuss ethical implications of personal branding for both scholarly work and practice. In conclusion, we outline a further research agenda for studying personal branding as a critical career and organizational behavior activity in contemporary working environment.